Impacto da segunda e terceira etapas do Método Canguru nas variáveis clínicas neonatais: do nascimento ao sexto mês de idade gestacional corrigida - Alves, Fernanda Nascimento (2019)
Introduction: Prematurity is still a challenge for perinatal care throughout the world. However, advances in the management of pre- and postnatal care, together with the technological increase of the Units of Neonatal Intensive Care Units (NICU), have significantly improved the quality of care provided to preterm newborns (PTNB) low weight and their families. Among these advances, one of the actions proposed by the Ministry of Health, the Standard of Humanized Care for Newborns of Low Weight - Kangaroo Method, published as public health policy, stands out. This policy was based on Kangaroo Mother Care, created in Colombia in 1978, an alternative to traditional care in which the PTNB was in skin-to-skin contact with the mother. Developed in three stages in Brazil, the Kangaroo Method (KM) aims to develop actions that favor family-centered care, reduce stressors to PTNB, promote breastfeeding and skin-to-skin contact through position kangaroo, in addition to strengthening the mother-child-family bond. The first stage of the KM takes place in the NICU, soon after the premature birth, in order to host the family, minimize stressors to the PTNB, promote the mother-child bond through touch, inclusion in care and kangaroo positioning whenever possible. The second stage occurs after stabilization of the PTNB in the Kangaroo Neonatal Intermediate Care Units, where the mother stays with the child 24 hours a day and performs skin-to-skin contact whenever possible. The third stage occurs after hospital discharge and consists of outpatient follow-up until the PTNB reaches a minimum weight of 2500 g. Studies, especially in the international literature, have demonstrated the benefits of skin-to-skin contact. However, the KM in Brazil encompasses other pillars besides the positioning. Thus, the objective of this study was to evaluate the impact of the second and third stages on neonatal clinical variables, specifically on exclusive breastfeeding rates, weight gain, hospitalization time and rehospitalization rates, from birth to sixth month of corrected gestational age . Materials and Methods: This is an observational, retrospective study with a quantitative approach. The study included very low birth weight infants (<1500 g) and documental evaluation was performed through the analysis of medical records. The 93 included PTNB were divided into two groups: GCCo (n = 53) - composed of PTNB attended at the Conventional Neonatal Intermediate Care Unit; GCCa (n = 36) – composed of those who were assisted in the Kangaroo Neonatal Intermediate Care Unit. Results: The Kangaroo Neonatal Intermediate Care Unit group presented higher results in the exclusive breastfeeding rates at hospital discharge (p = 0.00) and during outpatient follow-up - first outpatient visit (p = 0.00) and fourth month of corrected gestational age (IGC) (p = 0.00) and lower rates of use of milk formula (p = 0.00) and readmission rate (p = 0.03). Conclusion: The second and third stages of KM had a positive impact in relation to exclusive breastfeeding, the use of milk formula, maintenance of weight gain and readmission rates. Other studies that consider other clinical variables of equal importance are necessary.